Sodium-ion battery positive electrode material with stable circulation and preparation method of sodium-ion battery positive electrode material

By using N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)ureabislauramide/copper complex as interface modifiers in sodium ion battery positive electrode materials, the structural problem of the sodium ion battery positive electrode materials is solved, and the cycle stability and energy density of the battery are improved.

CN119674039APending Publication Date: 2025-03-21ZHEJIANG SHANGAO NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411955881.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The structural problems of the positive electrode material of existing sodium ion batteries lead to poor discharge capacity and cycling performance, hindering the development of sodium ion batteries.

Method used

A cyclic stable sodium ion battery cathode material and its preparation method are used. The electrochemical performance and stability of the cathode material are improved by wet ball milling and high-temperature calcining process, combined with N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide/copper complex as an interface modifier.

Benefits of technology

It effectively improves the discharge specific capacity, charge and discharge efficiency and cycle retention rate of sodium ion batteries, improves the electrochemical performance of the surface of the positive electrode material, and improves the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery positive electrode material with stable circulation and a preparation method thereof, and relates to the field of sodium-ion batteries. The preparation method comprises the following specific steps: adding a sodium source, ferrous salt, a carbon source and an interface modifier into a polytetrafluoroethylene ball milling tank, performing wet ball milling, transferring into a tubular furnace after ball milling, performing high-temperature calcination, and cooling to room temperature to obtain a sintered material; and weighing a sodium source again, mixing the sodium source with the sintered material, carrying out wet ball milling, transferring into a tubular furnace after ball milling, carrying out high-temperature calcination, and cooling to room temperature to obtain the sodium ion battery positive electrode material. The method improves the electrochemical performance of the surface of the positive electrode material, and improves the energy density and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material with stable circulation and a preparation method thereof. Background Art

[0002] At present, with the increasing demand in the field of power batteries, the materials of lithium-ion batteries are in short supply, and the research on room-temperature sodium-ion batteries has emerged. In terms of key performance such as battery energy density and number of cycles, positive electrode materials play a very critical role. Generally, positive electrode materials need to have high specific capacity (affecting energy density), abundant resources (affecting cost), stable structure (the structure does not undergo phase change or the phase change is highly reversible during the sodium ion insertion and extraction process) and high operating voltage (affecting energy density). At present, the most studied positive electrode materials for sodium-ion batteries are mainly: transition metal oxides, Prussian blue / white compounds, and polyanion compounds.

[0003] A method for reducing the residual alkali content on the surface of a sodium ion battery layered positive electrode material, a sodium ion battery positive electrode material, and a sodium ion battery (Chinese patent application number: CN202310481328.9) The method for reducing the residual alkali content on the surface of a sodium ion battery layered positive electrode material comprises the following steps: S1, dispersing sodium difluorophosphate in a first organic solvent to prepare a sodium difluorophosphate solution; S2, placing the sodium ion battery layered positive electrode material to be treated in a mixer, and then adding the sodium difluorophosphate solution to the mixer and mixing it with the sodium ion battery layered positive electrode material to be treated; S3, performing solid-liquid separation on the mixed liquid to obtain a solid, then washing it, and finally drying it to obtain the treated sodium ion battery layered positive electrode material.

[0004] The sodium ion battery positive electrode material precursor described in the sodium ion battery positive electrode material precursor and preparation method thereof, sodium ion battery positive electrode material, sodium ion battery and electrical equipment (Chinese patent application number: CN202211188250.3) has a chemical formula of Ni x Mn y Fe1 -x-y (OH) 2 , wherein 0.15≤x≤0.35, 0.2≤y≤0.5; the S element content in the sodium ion battery positive electrode material precursor is ≤4000ppm, and the Na / S mass ratio is ≤1.5. The prepared positive electrode material has good element uniformity, few structural defects, controllable particle size and good sphericity.

[0005] Sodium ion battery composite positive electrode material and preparation method thereof, sodium ion battery positive electrode and sodium ion battery (Chinese patent application number: CN202211019828.2) The sodium ion battery composite positive electrode material comprises an inner core and an outer shell coated outside the inner core, wherein the inner core is a transition metal sodium-containing oxide, and the outer shell is a transition metal sodium-containing phosphide. The sodium ion battery composite positive electrode material of the present invention is obtained by ball-milling NaH2PO4, transition metal hydroxide nanoparticles and transition metal sodium-containing oxide, heating them under nitrogen or carbon dioxide or argon, and then calcining them.

[0006] However, the structural problems of the positive electrode materials in the existing sodium battery technology have affected the discharge capacity and cycle performance of the sodium ion battery, hindering the development of the sodium ion battery. Summary of the invention

[0007] The main purpose of the present invention is to provide a sodium ion battery positive electrode material with stable cycle and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0008] Another object of the present invention is to provide a sodium ion battery positive electrode material prepared by the above method.

[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a sodium ion battery positive electrode material with stable circulation and a preparation method thereof, and the operation steps are as follows: Step 1: According to the mass proportions, weigh 20-50 parts of sodium source, 45-65 parts of ferrous salt, 2-6 parts of carbon source and 0.02-0.2 parts of interface modifier, add them into a polytetrafluoroethylene ball mill, perform wet ball milling, transfer to a tube furnace for high-temperature calcination after ball milling, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 15-45 parts of sodium source and mix with sintering material, wet ball mill, transfer to a tubular furnace for high-temperature calcination after ball milling, and obtain a sodium ion battery positive electrode material after cooling to room temperature.

[0010] In one embodiment of the present invention, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium phosphate, sodium acetate, sodium nitrate and sodium sulfate.

[0011] In one embodiment of the present invention, the ferrous salt is selected from at least one of ferrous sulfate, ammonium ferrous sulfate, ferrous nitrate and ferrous chloride.

[0012] In one embodiment of the present invention, the carbon source is selected from at least one of carbon nanotubes, graphene, acetylene black, and conductive carbon black.

[0013] In one embodiment of the present invention, the interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and the preparation method thereof is as follows: In a stirred tank, 12-24 parts of 2-isocyanate pyridine, 3-7 parts of cupric chloride, and 200-300 parts of N,N-dimethylformamide are added by weight, and the mixture is stirred at 40-50° C. for 100-150 minutes. Then, 24-48 parts of N-(2-hydroxyethyl) dodecylamide, 0.002-0.05 parts of 1,1'-bis(1-hydroxyethyl) ferrocene, and 0.1-1 parts of dimethyltin as a catalyst are added, and the mixture is stirred at 60-80° C. for 30-60 minutes. N,N-dimethylformamide is removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

[0014] In one embodiment of the present invention, the wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:1.5-2:0.8-1.2; the ball milling speed is 80-160rpm, and the ball milling time is 100-200mins.

[0015] In one embodiment of the present invention, the high temperature calcination temperature is 300-420°C, and the high temperature calcination time is 4-8h.

[0016] In one embodiment of the present invention, the heating rate of the tubular furnace is 1-4°C / min.

[0017] In one embodiment of the present invention, the tube furnace is filled with an inert gas, including but not limited to nitrogen, argon, and helium.

[0018] The reaction mechanism of the above interfacial modifiers: 1. 2-Isocyanate pyridine reacts with N-(2-hydroxyethyl) dodecylamide to generate N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea dilauramide.

[0019] 2.2-Isocyanate pyridine reacts with 1,1'-bis(1-hydroxyethyl)ferrocene to form an addition reaction. 3. Then it reacts with copper chloride to form a copper complex.

[0020] 4. The above two products are mixed to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex.

[0021] Technical effects: 1. Improve the electrochemical properties of positive electrode materials: N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex can be used as an interface modifier to improve the electrochemical properties of the positive electrode material surface and improve the energy density and cycle stability of the battery.

[0022] 2. Improve the stability of positive electrode materials: The interfacial modifier can form a protective film on the surface of the positive electrode material to prevent direct contact between the positive electrode material and the electrolyte, reduce the occurrence of side reactions, and thus improve the stability of the positive electrode material.

[0023] 3. Environmental protection: The solvent N,N-dimethylformamide used in the preparation method can be recovered by distillation, reducing the impact on the environment. DETAILED DESCRIPTION

[0024] In view of the deficiencies in the prior art, the inventor of this case, after long-term research and extensive practice, was able to propose the technical solution of the present invention. The technical solution, its implementation process and principle, etc. will be further explained as follows.

[0025] Example 1 A sodium ion battery positive electrode material with stable circulation and a preparation method thereof, wherein the operation steps are as follows: Step 1: Weigh 20g of sodium source, 45g of ferrous salt, 2g of carbon source and 0.02g of interface modifier, add them into a polytetrafluoroethylene ball mill, wet-mill, transfer to a tube furnace for high-temperature calcination, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 15 g of sodium source and mix it with the sintering material, wet-mill it, transfer it to a tubular furnace for high-temperature calcination, and cool it to room temperature to obtain the positive electrode material for the sodium ion battery.

[0026] The sodium source is selected from sodium carbonate.

[0027] The ferrous salt is selected from ferrous sulfate.

[0028] The carbon source is selected from carbon nanotubes.

[0029] The interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and its preparation method is as follows: 12 g of 2-isocyanate pyridine, 3 g of cupric chloride, and 200 g of N,N-dimethylformamide were added to a stirring kettle, and the mixture was stirred at 40° C. for 100 minutes. Then, 24 g of N-(2-hydroxyethyl) dodecylamide, 0.002 g of 1,1'-bis(1-hydroxyethyl) ferrocene, and 0.1 g of dimethyltin as a catalyst were added. The mixture was stirred at 60° C. for 30 minutes, and N,N-dimethylformamide was removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

[0030] The wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:1.5:0.8; the ball milling speed is 80 rpm, and the ball milling time is 100 minutes.

[0031] The high temperature calcination temperature is 300°C and the high temperature calcination time is 4h.

[0032] The heating rate of the tube furnace is 4°C / min.

[0033] The tube furnace is filled with an inert gas, including but not limited to nitrogen.

[0034] Example 2 A sodium ion battery positive electrode material with stable circulation and a preparation method thereof, wherein the operation steps are as follows: Step 1: weigh 30g of sodium source, 50g of ferrous salt, 3.5g of carbon source and 0.08g of interface modifier, add them into a polytetrafluoroethylene ball mill, wet-mill, transfer to a tube furnace for high-temperature calcination, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 25 g of sodium source and mix it with the sintering material, wet ball mill it, transfer it to a tubular furnace for high-temperature calcination after ball milling, and obtain the positive electrode material of the sodium ion battery after cooling to room temperature.

[0035] The sodium source is selected from sodium bicarbonate.

[0036] The ferrous salt is selected from ammonium ferrous sulfate.

[0037] The carbon source is selected from graphene.

[0038] The interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and its preparation method is as follows: 16 g of 2-isocyanate pyridine, 4.5 g of cupric chloride, and 235 g of N,N-dimethylformamide were added to a stirring kettle, and the mixture was stirred at 45° C. for 125 minutes. Then, 32 g of N-(2-hydroxyethyl) dodecylamide, 0.02 g of 1,1'-bis(1-hydroxyethyl) ferrocene, and 0.35 g of dimethyltin catalyst were added, and the mixture was stirred at 70° C. for 40 minutes. N,N-dimethylformamide was removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

[0039] The wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:1.8:1; the ball milling speed is 120 rpm, and the ball milling time is 135 mins.

[0040] The high temperature calcination temperature is 340°C and the high temperature calcination time is 6h.

[0041] The heating rate of the tube furnace is 3°C / min.

[0042] The tube furnace is filled with an inert gas, including but not limited to nitrogen.

[0043] Example 3 A sodium ion battery positive electrode material with stable circulation and a preparation method thereof, wherein the operation steps are as follows: Step 1: Weigh 40g of sodium source, 55g of ferrous salt, 5g of carbon source and 0.15g of interface modifier, add them into a polytetrafluoroethylene ball mill, wet-mill, transfer to a tube furnace for high-temperature calcination, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 35 g of sodium source and mix it with the sintering material, wet-mill it, transfer it to a tubular furnace for high-temperature calcination after ball milling, and obtain the positive electrode material of the sodium ion battery after cooling to room temperature.

[0044] The sodium source is selected from sodium phosphate.

[0045] The ferrous salt is selected from ferrous nitrate.

[0046] The carbon source is selected from acetylene black.

[0047] The interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and its preparation method is as follows: 20 g of 2-isocyanate pyridine, 6 g of cupric chloride, and 270 g of N,N-dimethylformamide were added to a stirring kettle, and the mixture was stirred at 45° C. for 125 minutes. Then, 42 g of N-(2-hydroxyethyl) dodecylamide, 0.035 g of 1,1'-bis(1-hydroxyethyl) ferrocene, and 0.75 g of dimethyltin catalyst were added, and the mixture was stirred at 70° C. for 50 minutes. N,N-dimethylformamide was removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

[0048] The wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:2:0.9; the ball milling speed is 140 rpm, and the ball milling time is 175 mins.

[0049] The high temperature calcination temperature is 380°C and the high temperature calcination time is 6h.

[0050] The heating rate of the tube furnace is 2°C / min.

[0051] The tube furnace is filled with an inert gas, including but not limited to argon.

[0052] Example 4 A sodium ion battery positive electrode material with stable circulation and a preparation method thereof, wherein the operation steps are as follows: Step 1: weigh 50g of sodium source, 65g of ferrous salt, 6g of carbon source and 0.2g of interface modifier, add them into a polytetrafluoroethylene ball mill, wet-mill, transfer to a tube furnace for high-temperature calcination, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 45 g of sodium source and mix it with the sintering material, wet-mill it, transfer it to a tubular furnace for high-temperature calcination after ball milling, and obtain the positive electrode material of the sodium ion battery after cooling to room temperature.

[0053] The sodium source is selected from sodium acetate.

[0054] The ferrous salt is selected from ferrous chloride.

[0055] The carbon source is selected from conductive carbon black.

[0056] The interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and its preparation method is as follows: 24 g of 2-isocyanate pyridine, 7 g of cupric chloride, and 300 g of N,N-dimethylformamide were added to a stirring kettle, and the mixture was stirred at 50° C. for 150 minutes. Then, 48 g of N-(2-hydroxyethyl) dodecylamide, 0.05 g of 1,1'-bis(1-hydroxyethyl) ferrocene, and 1 g of dimethyltin as a catalyst were added. The mixture was stirred at 80° C. for 60 minutes, and N,N-dimethylformamide was removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

[0057] The wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:2:0.9; the ball milling speed is 160 rpm, and the ball milling time is 200 mins.

[0058] The high temperature calcination temperature is 420°C and the high temperature calcination time is 8h.

[0059] The heating rate of the tube furnace is 1°C / min.

[0060] The tube furnace is filled with an inert gas, including but not limited to helium.

[0061] Comparative Example 1 This comparative example is consistent with Example 1, and will not be described in detail here. The difference from Example 1 is that no interface modifier is added during the preparation of the positive electrode material for the sodium ion battery.

[0062] Comparative Example 2 This comparative example is consistent with Example 1, and will not be described in detail here. The difference from Example 1 is that cupric chloride is not added during the preparation of the interface modifier.

[0063] Comparative Example 3 This comparative example is consistent with Example 1, and will not be described in detail here. The difference from Example 1 is that 1,1'-bis(1-hydroxyethyl)ferrocene is not added during the preparation of the interface modifier.

[0064] Example Testing Preparation of sodium-ion batteries Preparation of positive electrode sheets: respectively take the sodium ion battery positive electrode materials prepared in the comparative examples of each embodiment, the conductive agent is conductive carbon black, and the binder is polyvinylidene fluoride, mix the sodium ion battery positive electrode material, the conductive agent, and the binder in a mass ratio of 90:5:5, dissolve the mixed materials in N-methylpyrrolidone solvent, grind into slurry, coat it on aluminum foil, and dry it at 120°C for 12 hours to obtain a positive electrode sheet.

[0065] Preparation of button batteries: sodium metal sheets were used as negative electrode sheets, glass fiber was used as separators, the solutes of the electrolyte were 1 mol / L sodium perchlorate and 5 wt% vinylene carbonate, and the solvents were ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1. The positive electrode sheets, separators, negative electrode sheets, gaskets, and springs were installed in the order of CR2023 button batteries, 100 μL of electrolyte was injected, and the button batteries were obtained after packaging.

[0066] The button cells prepared with the positive electrode materials of the above embodiment and the comparative example were tested for charge and discharge, and the test results are as follows: Table 1 First cycle discharge capacity (mAh / g) First charge and discharge efficiency (%) 1C rate cycle 100 cycles retention rate (%) Example 1 90.35 99.08 99.61 Example 2 91.60 99.32 99.73 Example 3 92.48 99.46 99.80 Example 4 93.02 99.55 99.89 Comparative Example 1 75.54 95.14 96.88 Comparative Example 2 81.12 97.20 98.12 Comparative Example 3 83.77 97.91 98.75 From the test results of the above specific implementation plan, it can be seen that this method effectively improves the discharge capacity, charge and discharge efficiency and cycle retention rate of sodium ion batteries, improves the electrochemical properties of the surface of the positive electrode material, and improves the energy density and cycle stability of the battery.

[0067] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A cyclically stable sodium ion battery cathode material and a preparation method thereof, wherein the operation steps are as follows: Step 1: According to the mass proportions, weigh 20-50 parts of sodium source, 45-65 parts of ferrous salt, 2-6 parts of carbon source and 0.02-0.2 parts of interface modifier, add them into a polytetrafluoroethylene ball mill, perform wet ball milling, transfer to a tube furnace for high-temperature calcination after ball milling, and obtain a sintered material after cooling to room temperature; Step 2: Weigh 15-45 parts of sodium source and mix with sintering material, wet ball mill, transfer to a tubular furnace for high-temperature calcination after ball milling, and obtain a sodium ion battery positive electrode material after cooling to room temperature.

2. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium phosphate, sodium acetate, sodium nitrate and sodium sulfate.

3. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The ferrous salt is selected from at least one of ferrous sulfate, ammonium ferrous sulfate, ferrous nitrate and ferrous chloride.

4. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The carbon source is selected from at least one of carbon nanotubes, graphene, acetylene black and conductive carbon black.

5. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The interface modifier is N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl)urea bislauramide / copper complex, and its preparation method is as follows: In a stirred tank, 12-24 parts of 2-isocyanate pyridine, 3-7 parts of cupric chloride, and 200-300 parts of N,N-dimethylformamide are added by weight, and the mixture is stirred at 40-50° C. for 100-150 minutes. Then, 24-48 parts of N-(2-hydroxyethyl) dodecylamide, 0.002-0.05 parts of 1,1'-bis(1-hydroxyethyl) ferrocene, and 0.1-1 parts of dimethyltin as a catalyst are added, and the mixture is stirred at 60-80° C. for 30-60 minutes. N,N-dimethylformamide is removed by distillation to obtain N,N'-bis(2-hydroxyethyl)-N,N'-bis(pyridin-2-yl) urea bislauramide / copper / iron complex.

6. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The wet ball milling process parameters are as follows: the mass ratio of the mixture, the ball milling zirconium beads and the ethanol is 1:1.5-2:0.8-1.2; the ball milling speed is 80-160 rpm, and the ball milling time is 100-200 mins.

7. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The high temperature calcination temperature is 300-420°C, and the high temperature calcination time is 4-8h.

8. The sodium ion battery positive electrode material with stable cycle and the preparation method thereof according to claim 1, characterized in that: The heating rate of the tubular furnace is 1-4°C / min.

9. A cyclically stable sodium ion battery positive electrode material and a preparation method thereof according to claim 1, characterized in that: The tube furnace is filled with inert gas, including but not limited to nitrogen, argon and helium.

Citation Information

Patent Citations

  • Sodium-ion battery composite positive electrode material and preparation method thereof, sodium-ion battery positive electrode and sodium-ion battery

    CN115275156A

  • Sodium-ion battery positive electrode material precursor and preparation method thereof, sodium-ion battery positive electrode material, sodium-ion battery and electric equipment

    CN115504522A

  • Method for reducing residual alkali content on the surface of sodium ion battery layered positive electrode material, sodium ion battery positive electrode material and sodium ion battery

    CN116495800B